Urban Zoning Guidelines for the Management and Protection of Underground Water of the Birris River Watershed (Cartago) - Ramírez, Pablo (2011)
The Birrís watershed is located in the southeast slope of the Irazú volcano, in it, exist several hydrogeological units composed by volcanic material, lahar flow and ash, which behave as aquifer and acuitards contained in two denominated aquifer systems Birrís and Pacayas-Reventado, which present an effluent hydraulic connection with the superficial drainages. Considering the use of the current soil, the recharge of the aquifer systems is of 38 000 000 m3/year. In this basin, the current use of the land doesn't coincide with the use capacity, this way 66% of the area is in overuse, impacting negatively to the aquifer systems, because it has happened conversion from the forest areas to shepherding areas and annual cultivations in the sectors bordering to the main springs. The proposal of limits for the handling of the basin includes among other things: a) a reforestation plan in areas with capacity of forest use, recharge areas and of protection of beds in the whole basin; b) the areas of recharge of the springs of the basin in a such way should be protected; c) classes of use of the territory like lineal parks should be established, areas of low density, protected areas, bioturistics corridors; d) classify the potential sources of contamination and the measures of prevention; and) in general a plan of classification of the basin should be promoted that reconciles the water production of the same one with its use capacity.